2005
DOI: 10.1097/00001199-200501000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of Pharmacology

Abstract: During the past 20 years in pharmacology, a number of innovations have appeared that have resulted in significant changes in the drugs available for people with traumatic brain injury. Among the anticonvulsants, antidepressants, and antipsychotics, new drugs have appeared with fewer cognitive side effects. In these classes of drugs, as well as among central nervous system stimulants, once-daily or other sustained-release preparations have been introduced that make it considerably more likely that the patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Its mechanism in humans remains poorly understood; however, animal models have shown that trazodone inhibits serotonin re-uptake [78]. For TBI patients, trazodone is generally well tolerated and unlike the tricyclic antidepressants, has little to no anticholinergic effect [81]. Compared to Z-drugs, trazodone has a relatively longer half-life at 5–9 h, so daytime sedation is a potential side effect [81].…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its mechanism in humans remains poorly understood; however, animal models have shown that trazodone inhibits serotonin re-uptake [78]. For TBI patients, trazodone is generally well tolerated and unlike the tricyclic antidepressants, has little to no anticholinergic effect [81]. Compared to Z-drugs, trazodone has a relatively longer half-life at 5–9 h, so daytime sedation is a potential side effect [81].…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
“…For TBI patients, trazodone is generally well tolerated and unlike the tricyclic antidepressants, has little to no anticholinergic effect [81]. Compared to Z-drugs, trazodone has a relatively longer half-life at 5–9 h, so daytime sedation is a potential side effect [81]. Despite trazodone’s usage, there are no clinical trials on trazodone for insomnia treatment in the TBI population.…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For individuals with memory problems, a sustained release version of methylphenidate may help circumvent the problems associated with inconsistent adherence to the medication regimen. Metadate (effective for 8 -10 hr) and Concerta (effective for about 12 hr) are long-acting forms of methylphenidate and are both possibilities for use in TBI, although no research has evaluated their effectiveness in this population to date (Glenn & Wroblewski, 2005).…”
Section: Monoaminergic Stimulant Agentsmentioning
confidence: 99%
“…However, the effects of these alternative remedies are difficult to interpret. The standardization and purity of these extracts vary because they lack regulation by the Food and Drug Administration [28]. In addition, many of these alternative medications are readily available and do not require physician inquiry.…”
Section: Introductionmentioning
confidence: 99%